The Effectiveness of Speed Training on the Physiological Characteristics of Athletes in Youth Pencak Silat in the Competing and Art Categories - Adhe Saputra; Ahmad Muzaffar (JUARA : Jurnal Olahraga, 2022)
Performance of cardiovascular endurance, explosive power, and agility are the most crucial types of physical conditions in the sport of Pencak silat. Research on the effects of specific exercises on performance in the sport of Pencak silat is still limited. Therefore, this study aimed to assess the impact of speed training for six weeks on the performance of cardiovascular endurance, explosive power, and agility of adolescent Pencak silat athletes in the fighting and art categories. The experimental method with pretest and post-test approaches without a control group design is used in this study. The total subjects were 30 male Pencak silat athletes who were divided into two groups (15 fighter athletes and 15 arts athletes) with an average age of 18.53 ± 2.13 years, body weight 62.74 ± 4.18 kg, height 168.78 ± 3.82, BMI 22.04 ± 1.82, and FAT 10.55 ± 1.29%. Subjects were recruited based on inclusion criteria, including not smoking, not consuming alcohol, not being on drug intervention and having a minimum of 3 years of practice. The results showed that speed training (sprint) for six weeks significantly affected VO2max, agility and leg muscle strength in Pencak silat athletes. Thus, the findings in this study can be used as a reference for Pencak silat coaches and athletes in improving the aerobic and anaerobic performance of athletes.